2011
DOI: 10.1111/j.1399-0012.2009.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sleep-related breathing disorder in patients with end-stage renal disease after kidney transplantation

Abstract: Sleep-related breathing disorder (SRBD) is a common symptom of end-stage renal disease (ESRD). The aim of this study was to determine whether kidney transplantation improves SRBD. Twenty-four patients with ESRD, who were admitted for kidney transplantation, underwent a sleep study using a portable ventilation effort recorder on the night before transplantation. Of these patients, 20 could repeat the overnight monitoring two wk after the transplantation. The median apnea-hypopnea index (AHI) of the 20 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
0
9
1
2
Order By: Relevance
“…The present study detected that the median value of AHI was 1.2 (range 0e28.9), which decreased to 0.4 (range 0–7) (p = 0.034), which indicates that in addition to improvement in metabolic parameters there is a significant improvement in SDB after renal transplant. The results are in contrast to the studies by Beecroft et al [16] and Rodrigues et al [17], which showed no or minimal improvement in AHI after renal transplant, although the results are similar to those by Jurado-Gamez et al [18] and Lee et al [19], which showed significant improvement in AHI post-transplant.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The present study detected that the median value of AHI was 1.2 (range 0e28.9), which decreased to 0.4 (range 0–7) (p = 0.034), which indicates that in addition to improvement in metabolic parameters there is a significant improvement in SDB after renal transplant. The results are in contrast to the studies by Beecroft et al [16] and Rodrigues et al [17], which showed no or minimal improvement in AHI after renal transplant, although the results are similar to those by Jurado-Gamez et al [18] and Lee et al [19], which showed significant improvement in AHI post-transplant.…”
Section: Discussioncontrasting
confidence: 94%
“…We could find only four studies that have examined the effect of transplant on SDB in patients with ESRD; three of these studies have been carried out using PSG; one each from Canada (n = 18) [16], Spain (n = 9) [18], and Brazil (n = 34) [17], while one has additionally been carried out using portable ventilation recorder in South Korea (n = 20) [19]. Our sample size (n = 18) is similar to the ones in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, preventing hypervolemia in the patients with ESRD can significantly improve OSA and resistant hypertension. In a trial where a sleep study was performed before and after transplant, there was a significant decrease in AHI in OSA patients after transplant [70] . In another study, renal transplantation was found to ameliorate sleep disturbances and lead to improvement of sleep architecture [71] .…”
Section: Role Of Renal Replacement Therapymentioning
confidence: 99%
“…Einige Studien ergeben Hinweise darauf, dass sich die SBAS nach einer Nierentransplantation verbessern, andere Studien konnten keinen Einfluss belegen [8,16]. Allerdings sind die bislang untersuchten Patientenkollektive relativ klein und die Studienprotokolle selten vergleichbar, sodass eine grundsätzliche Aussage nicht möglich scheint.…”
Section: Einfluss Einer Nierentransplantationunclassified